Client Accounts of Corrective Experiences in Psychotherapy: Implications for Clinical Practice. Issue 2 (28th November 2016) - Angus, Lynne; Constantino, Michael J.
Abstract : The Patient Perceptions of Corrective Experiences in Individual Therapy (PPCEIT; Constantino, Angus, Friedlander, Messer, & Moertl, 2011) posttreatment interview guide was developed to provide clinical researchers with an effective mode of inquiry to identify and further explore clients' firsthand accounts of corrective and transformative therapy experiences and their determinants. Not only do findings from the analysis of client corrective experience (CE) accounts help identify what and how CEs happen in or as a result of psychotherapy, but the measure itself may also provide therapists with an effective tool to further enhance clients' awareness, understanding, and integration of transformative change experiences. Accordingly, we discuss in this afterword to the series the implications for clinical practice arising from (a) the thematic analysis of client CE accounts, drawn from a range of clinical samples and international research programs and (b) the clinical effect of completing the PPCEIT posttreatment interview inquiry. We also identify directions for future clinical training and research.